Governance and Purchasing Function under Social Health Insurance in Nepal: Looking Back and Moving Forward - Sapkota, Vishnu Prasad; Bhusal, Umesh Prasad (Journal of Nepal Health Research Council, 2017)
Nepal is pursuing Social Health Insurance as a way of mobilizing revenues to achieve Universal Health Coverage. The Social Health Insurance governance encourages service providers to maintain quality and efficiency in services provision by practicing strategic purchasing. Social Health Security Programme is a social protection program which aspires to achieve the goals of Social Health Insurance. Social Health Security Development Committee needs to consider following experiences to function as a strategic purchaser. The Social Health Security Development Committee need to be an independent body instead of falling under Ministry of Health. Similarly, purchasing of health services needs to be made strategic, i.e., Social Health Security Development Committee should use its financial power to guide the provider behavior that will eventually contribute to achieving the goals of quality and efficiency in service provision. The other social health security funds should be merged with Social Health Security Development Committee and develop a single national fund. Finally, the state has to regulate and monitor the performance of the SHI agency.